Sistem Pendukung Keputusan Pemilihan Kayu Dalam Konstruksi Atas Rumah Dengan Aspek Kualitas Dan Keberlanjutan Menggunakan Metode Weighted Sum Model Studi Kasus Pada CV Persada Sejahtera Kabupaten Ponorogo - deni sulistyo sumboro (LPPM Universitas Merdeka Madiun, 2024)
House constuction is one of the main aspects of infrastructure development in various parts of the world. A house is not only a residence for individuals and families, but also reflects environmental sustainability and the cultural values of the local community. Therefore, selecting the right construction materials is crucial in ensuring the success of an efficient and sustainable home building project. The aim of this research is to design and build a decision support system for wood selection in the construction of house structures with quality and sustainability aspects using the Weighted Sum Model method. The decision support system using the Weighted Sum Model method was chosen because in its solution the ranking results of the WSM method are objective, so that it can provide fairness in decision making and can provide better results than conventional methods. The results of testing the DSS application using Black Box Testing, based on this test, the results obtained were as expected and valid. In this research, the user role is only for admin, for future researchers it can be developed by adding roles for users such as roles for company owners.